Structure and chemical durability improvement of alkali silicate glass by zirconium dioxide and erbium oxide addition - DENPRAWAT, ATIVIT; SINWANASARP, Kittipong; KIDKHUNTHOD, Pinit; LAORODPHAN, Nattapol; THIEMSORN, Worapong (Journal of Metals, Materials and Minerals, 2023)
Glass structure tailoring of alkali silicate glasses by addition of ZrO2 and Er2O3 is found to enhance the chemical durability of glasses. ZrO2 (x ranged between 5 mol% to 15 mol%) and Er2O3 (y ranged between 0.5 mol% to 1.5 mol%) were used to replace SiO2 and Na2O, respectively, in the glasses with the nominal composition of 10Li2O-(15-y)Na2O-10CaO-(65-x)SiO2-xZrO2-y Er2O3. The samples were prepared by conventional melt quenching technique. The structures of produced glasses were examined by X-ray absorption spectroscopy (XAS) and Raman spectroscopy. XAS spectra demonstrated that the oxidation numbers of Zr and Er ions were +4 and +3, respectively. The chemical environment around both cations was six-fold coordination. In addition, Raman spectra demonstrated that the Zr4+ ions formed the Q4(Zr) structure, which caused the reduction of non-bridging oxygen. In case of the Er3+ ions, the formation of the Si-O-Er bonds was explained from the Raman study. The chemical durability of glass was determined from Na+ ions leaching values. In pH 7 solution, the leached Na+ ions reduced from 25.67% to 21.43% and from 22.50% to 20.49% as a function of concentration of ZrO2 (x = 5 mol% to 15 mol%) and Er2O3 (y = 0.5 mol% to 1.5 mol%), respectively. As the results, the chemical durability of the ZrO2-containing and Er2O3-containing glasses were significantly improved due to charge compensated mechanism and enhancing network rigidity by increasing cation field strength. Moreover, the micro-hardness (580 HV to 837 HV) and density (2.54 g⸳cm-3 to 2.82 g⸳cm-3) also displayed an increased tendency with larger concentration of ZrO2 and Er2O3.